Uji Aktivitas Antijamur Ekstrak Biji Keben (Barringtonia asiatica (L.) Kurz) terhadap Curvularia verruculosa Penyebab Penyakit Bercak Curvularia pada Tanaman Padi (Oryza sativa L.) - WIBAWA, I GEDE KARTA SATRIA; SUPRAPTA, DEWA NGURAH; KHALIMI, KHAMDAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2018)
Antifungal Activity of Keben (Barringtonia asiatica (L.) Kurz) Seed Extract against Curvularia verruculosa the Causal Agent of Curvularia Leaf Spot Disease on Rice (Oryza sativa L.) This research was conducted to determine the effectiveness of keben (Barringtonia asiatica (L.) Kurz) seed extract to control Curvularia verruculosa the causal agent of curvularia leaf spot disease on rice. The extract concentration of 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% and 1.0% was tested on in vitro test to determine the minimum inhibitory concentration (MIC) and inhibition percentage. Crude seed extract was partitioned and analyzed using GC-MS to determine the active antifungal compound. Concentration of 0.6%, 0.7%, 0.8%, 0.9% and 1.0% is tested on in vivo test in a greenhouse to determine the effectiveness of keben seed extract formula to control the curvularia leaf spot disease on rice. The result shows that the MIC of keben seed extract was 0.5% with inhibitory percentage that increases from 0.1% to 0.5% and cause 100% inhibitory on 0.6% concentration and above. GC-MS analysis showed antifungal compound such as Butyl Hydroxy Toluene; Dodecanoic acid, methyl ester; Methyl tetradecanoate; Benzoic acid 2, 5-bis (trimethylsiloxy)-trimethylsilyl ester; 1-Tetradecanol; Hexadecanoic acid, methyl ester; Octasiloxane, 1, 1, 3, 3, 5, 5, 7, 7, 9, 9, 11, 11, 13, 13, 15, 15-hexadecamethyl-; 13-Docosenoic acid, methyl ester (Z)- and 1, 2-Benzenedicarboxylic acid, dioctyl ester are present in keben seed. Greenhouse test showed that keben seed extract can suppress curvularia leaf spot disease from 25.16% to 2.57%.